Performance evaluation and clinical validation of optimized nucleotide MALDI-TOF-MS for mycobacterial identification - Li, Baiying; Zhu, Chi; Sun, Lifang; Dong, Hang; Sun, Yaping; Cao, Shangzhi; Zhen, Libo; Qi, Qi; Zhang, Quanquan; Mo, Ting; Wang, Huijie; Qiu, Meihua; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Objective To evaluate the performance and validate the diagnostic value of a nucleotide matrix-assisted laser desorption time-of-flight mass spectrometry (MALDI-TOF-MS) with the analysis process optimized in identification of mycobacterium species. Methods The optimized analysis process was used for mycobacterial identification in the nucleic MALDI-TOF-MS. 108 samples were used for assessing the performance of nucleic MALDI-TOF-MS, including 25 reference standards, 37 clinical isolates, 37 BALF, and 9 plasmids. The BALF of 38 patients suspected of pulmonary mycobacterial infection was collected for validation. Clinical etiological diagnosis was used as the gold standard to evaluate the diagnostic value of nucleotide MALDI-TOF-MS. Results The sensitivity, specificity, and accuracy of the nucleotide MALDI-TOF-MS in mycobacterial identification were 96.91%, 100% and 97.22%, respectively, and the limit of detection for mycobacterium tuberculosis (MTB) was 50 bacteria/mL. Among 38 patients suspected of pulmonary mycobacterial infection, 33 were diagnosed with pulmonary tuberculosis infection, and 5 with non-mycobacterial infection. In clinical validation, the positive rates of MALDI-TOF-MS, Xpert MTB/RIF, culture and AFS in BALF of patients diagnosed with tuberculosis infection were 72.7%, 63.6%, 54.5% and 27.3%, respectively. The sensitivity/specificity of MALDI-TOF-MS, Xpert, culture and AFS in diagnosing MTB were 72.7%/100%, 63.6%/100%, 54.5%/100%, 27.3%/100%, with the areas under the curve of 0.864, 0.818, 0.773, and 0.636, respectively. Conclusion Optimized nucleotide MALDI-TOF-MS has satisfactory sensitivity, specificity and low LOD in the identification of mycobacteria, which may serve as a potential assay for mycobacterial identification.